1995
DOI: 10.1037/0735-7044.109.1.135
|View full text |Cite
|
Sign up to set email alerts
|

Importance of pup-related sensory inputs and maternal performance for the expression of Fos-like immunoreactivity in the preoptic area and ventral bed nucleus of the stria terminalis of postpartum rats.

Abstract: This study used Fos immunocytochemistry to locate neurons within the medial preoptic area (MPOA) and ventral bed nucleus of the stria terminalis (VBNST) that are tightly associated with the performance of maternal behavior in postpartum rats. In the first experiment, a high degree of Fos activation was observed in these regions if females were allowed to interact fully with pups, but not if they could receive only olfactory, visual, and auditory inputs from pups. The second experiment found that olfactory bulb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
107
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 60 publications
9
107
2
Order By: Relevance
“…On the other hand, electrical stimulation of the POA leads to shorter onset to maternal behaviors (30). Neuronal activation within the preoptic region, as measured by expression of the immediate early gene c-Fos, is significantly increased in animals exhibiting maternal behaviors (31)(32)(33)(34)(35)(36)(37)(38)(39). Importantly, estradiol implants within the preoptic region enhance the expression of maternal behaviors or decrease the latency to displaying maternal behaviors (2, 23, 29, 40, 41).…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, electrical stimulation of the POA leads to shorter onset to maternal behaviors (30). Neuronal activation within the preoptic region, as measured by expression of the immediate early gene c-Fos, is significantly increased in animals exhibiting maternal behaviors (31)(32)(33)(34)(35)(36)(37)(38)(39). Importantly, estradiol implants within the preoptic region enhance the expression of maternal behaviors or decrease the latency to displaying maternal behaviors (2, 23, 29, 40, 41).…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies revealed a contribution to this activation from trigeminal stimuli-necessary for retrieval and licking of pups Kolunie, 1989, 1991;Stern, 1996a,b)-but not rooting on the ventrum ; however, the reduced trigeminal contribution to Fos activation in the cPAG (Blomqvist and Craig, 1991) attributable to perioral anesthesia of the dam is compensated by prolonged kyphosis . Similar to expression of Fos in the medial amygdala or medial preoptic area (mPOA) after sex-or pup-related inputs from olfactory and somatosensory modalities (Baum and Everitt, 1992;Numan and Numan, 1995), the single elimination of one effective source of tactile contact with the litter, from snout or nipples, does not reduce Fos expression in the cPAG l,vl to the low levels seen in dams without physical access to pups.…”
Section: Effects Of Sk or Nsk Contact On Fos-ir Expression In The Pagmentioning
confidence: 99%
“…It has been noted, however, that many sites that contain Fos- and FosB-expressing cells in maternally behaving rats also express ERα [24, 30]. This is true when maternal behavior is tested soon after parturition at a time when the dams’ behavior has recently been under the influence of estradiol [20, 21]as well as many days later when the behavior is no longer hormone-dependent [13, 22, 23, 24, 25, 26, 27]. The presence of ERα in sites with elevated Fos-ir suggests the possibility that many of these neurons co-express Fos and ERα.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, direct physical contact with pups and receipt of tactile stimulation from them is necessary for this increase in immediate early gene activity [13, 20, 21, 22, 23, 24, 25, 26, 27]. Moreover, the genomic cascade initiated by activation of these immediate-early genes may be functionally significant for maternal behavior [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation